Peran Bhabinkamtibmas Dalam Mencegah Radikalisme Di Wilayah Hukum Polres Majalengka - Hendriko Silalahi (Indonesian Journal of Police Studies, 2020)
This research is motivated because the increase of the spread of radicalism in Majalengka Regency is increasing. Need to help the participation of members of the National Police to participate in the radicalism understanding debate by referring to the Regulation of the National Police Chief No. 3 of 2015. Prevention of understanding of radicalism is carried out through Bhabinkamtibmas activities and carried out with factors that support and support. The theory used to analyze these is the theory of communication, management theory. While the concepts used in this study are the concept of Bhabinkamtibmas, the concept of radicalism, and the concept of Community Policing. To analyze about lending between Bhabinkamtibmas and the community the writer uses the application of communication theory. While to analyze the opposite with the factors that influence the implementation of the Bhabinkamtibmas activities, the author uses the management theory of George R. Terry with 6 elements (humans, money, materials, methods, machines, markets). The research method uses qualitative obtained with the findings, observations, study documents, and interviews with information sources. Techniques used for data analysis include data reduction and working hypotheses by formulating a proportional question. The results of the study found that the implementation of Bhabinkamtibmas activities within the framework of preventing radicalism was not yet running optimally due to several influencing factors such as the Bhabinkamtibmas being involved in the duty of guarding the precincts as well as the police. In addition, infrastructure facilities are also inadequate. From the results of the field research, the authors suggest Satbinmas Majalengka to further improve the quality of human resources and complete infrastructure that can support the implementation of Bhabinkamtibmas activities in order to prevent radicalism in Majalengka Regional Police.